ANALISIS ISTINBA>T HUKUM ISLAM TERHADAP FATWA MAJELIS ULAMA INDONESIA (MUI) TENTANG JUAL BELI EMAS SECARA TIDAK TUNAI - Zainal Abidin (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2016)
Selling is a form of continuous experiencing muamalah development hand in hand with the development of the times and technology. This is evident with the rise of the trading system or method practiced by humans from time to time. As we know, in ancient times known system of barter or exchange of goods with the goods, then grew with the discovery of money to buy and sell, as we see in General. Even at this point, the human being easier with a system of buying and selling where one does not have to have the goods or money used to trade with other people, the system is commonly known to us with the credit system. However, the development of the system of buying and selling should be seen first if the system in accordance with Islamic teachings or not. One example is the system of buying and selling gold for no cash. At the time of the Prophet, selling the gold it can be when made in cash. But today, there are several products from some financial institutions that trade in gold in installments. It has certainly led to disquiet among the public. And as the solution, MUI set that may make selling gold is not the cash. It is certainly exciting to be scrutinized so that we know what base and method of istinba>t used MUI in setting such a fatwa.